Disulfiram neuropathy: two case reports. (December 2016) - Tran, Anh; Rison, Richard; Beydoun, Said
Abstract Background Neuropathy is a rare adverse side effect of disulfiram therapy and is under-recognized. There have been few case reports documenting this side effect. Case presentation Two cases of disulfiram peripheral neuropathy are discussed. The first case is that of a 25-year-old Caucasian woman who was exposed to disulfiram therapy for a total of 8 months and developed pain and stiffness that prevented her from walking. The second case is that of a 46-year-old Caucasian woman who developed sudden-onset numbness in her lower extremities with progression to pain. Her symptoms improved over the course of 2 months after cessation of disulfiram therapy. In both cases, symptoms improved after cessation of disulfiram therapy. Conclusions Disulfiram neuropathy occurs in persons with a history of chronic alcohol use. It is under-recognized and often attributed to alcoholic neuropathy given its comorbidity with alcoholic neuropathy. A greater understanding of this side effect may reduce neurologic complications related to disulfiram neuropathy and aid in early withdrawal of this offending agent.